Comparision between Two Different Files Systems and Two Different Obturating Techniques in Primary Teeth: An In Vivo Study - Dr. Bellapukonda Prudhvi Kumar; Dr. Kandarpa Balakrishna; Dr. Kandregula Chaitanya Ram; Dr. Bhagya Lakshmi Eluri; Dr. Matta Navya; Dr. Lavudu Bharathi (The Bioscan, 2025)
Aim: The aim of the study is to radiographically evaluate the quality of obturation of root canals of primary teeth subsequent to Biomechanical preparation with any two different file systems and two different obturation techniques. Materials and methods: Twenty teeth in subjects with mean age 8.7years were selected randomly using two different file systems and two different obturating techniques, i.e. Group 1: Manual K files & Reamers (20), Group 2: Manual K files & Navitips, (20) Group 3: Rotary kedo SG files & Reamers (20), Group 4: Rotary kedo SG files & Navitips (20). Quality of obturation and presence or absence of voids were assessed by taking radiographs after obturation was done using both the techniques. Results: Results of quality of obturation and voids were analyzed using Chi-square test. No statistically significant difference between two different files systems and two different Obturating Techniques (p > 0.05) was observed. However, higher voids were seen with the manual method with both the Reamer and Navitip files. Further, optimal fill was comparably higher with the Rotary method with both the files. Conclusion: Both the fie system and obturation techniques were found to be equally efficient statistically, though higher voids are seen through the manual method with both the Reamer and Navitip files and underfilling was seen with the Reamer files in both the manual and rotary methods (37.5, and 43.8% respectively)